Exigency Politics or New World Order? - Filipović, Miroslava (Panoeconomicus, 2011)
Since the onset of the current crisis, numerous intergovernmental organizations made declarations and plans, but only national packages were implemented to minimize adverse effects to real (national) economies. Despite the fact that capital markets have long ago become increasingly complex with a multitude of actors, a state-level approach remains firmly in place. This paper aims to present political responses to the crisis, identifying how politicians envision the future of capital markets and the world economy. The financial crisis might have been a direct motive to start a global political interplay regarding regulation, but it was also a unique opportunity for numerous actors to start pressing for their own agenda vis-à-vis the global economic and political order. Reviewing the responses of several of the most prominent actors on the scene may contribute to understanding how close the world is to having a new financial - or even economic - structure on the global level. Key words: Crisis, Capital markets, Regulation, Political agendas. JEL: F59, F02, G38, F21, F55, G15.